Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration (2007)
This study concerns the preparation and characterisation of microspheres associating alginate and two different types of hydroxyapatite (HA), which are intended to be used as drug delivery systems and bone regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using a chemical precipitation synthesis based on H3PO4, Ca(OH)2 and a surfactant, SDS (sodium dodecylsulphate), as starting reagents. These two powders of nanoHA and alginate were used to prepare two different types of microspheres. Both powders and microspheres were characterised using FTIR, TEM, SEM, mercury porosimetry analysis and X-ray diffraction Results show that pure hydroxyapatite (HA) and mixtures of HA/β-TCP in the nanometre range were obtained from both HA syntheses. Microspheres with different characteristics were obtained from these two types of hydroxyapatite.